2020
DOI: 10.1177/2158244020922970
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vehicle Ownership in Nigeria

Abstract: Vehicle ownership has increased tremendously in Nigeria for the past decades. This study determined factors that influence vehicle ownership intending to develop a more appropriate basis for forecasting vehicle ownership in the country. Multiple linear regression technique was used to identify the factors that influence vehicle ownership using national data from secondary sources. The results showed that four socioeconomic factors, namely, gross domestic product, per capita income, fuel price, and literacy lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…Collectively, this body of evidence suggests that there are differences between (and likely within) countries in variables that can influence travel mode choice, which may include access to motor vehicles, distance, and level of urbanization, among others. The lower prevalence of AT in our Nigerian sample may reflect the high rate of motorization in the state of Lagos [29] where data were collected.…”
Section: Active Transportationmentioning
confidence: 79%
“…Collectively, this body of evidence suggests that there are differences between (and likely within) countries in variables that can influence travel mode choice, which may include access to motor vehicles, distance, and level of urbanization, among others. The lower prevalence of AT in our Nigerian sample may reflect the high rate of motorization in the state of Lagos [29] where data were collected.…”
Section: Active Transportationmentioning
confidence: 79%
“…For example, we observe a high variability in motorcycle and three‐wheeler and other vehicle types depending on the culture and habits of different countries. However, it was not possible to capture such detailed distinctions in PRASTOF because insufficient data on the subject exist, with the literature mainly focusing on car ownership evolution (Dargay et al., 2007; Fishman et al., 2021; Kresnanto, 2019; Ma et al., 2019; Ukonze et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although many of such studies reported on the road transport energy consumption, only a few studies discussed the effects of fuel quality and vehicle technology on the environment; and air pollutant emissions are often not considered. On vehicle ownership, Ukonze et al [17] mention a gross domestic product, per capita income, fuel price, literacy level and stock of public transport vehicles as the determinants of vehicle ownership in Nigeria. The extent to which these vehicles stay on the road depends on vehicle mileage [18], economy [19], as well as users' travel-behavioural attitudes [20].…”
Section: A2mentioning
confidence: 99%
“…Oguchi and Fuse [42] provide an expression for the vehicle survival rate in Equation (17). However, the expression does not account for used imported vehicles and can only be applied to countries with a negligible number of used vehicle imports.…”
Section: Vehicle Survivabilitymentioning
confidence: 99%